Translation, Adaptation, and Validation of the Need for Cognition Scale–Short Form in the Greek Language for Secondary School Students - Georgiou, Yiannis; Kyza, Eleni A. (My University, 2018)
The purpose of the present study was to adapt and validate the Need for Cognition Scale–Short Form (NfC-SF) in the Greek language. A multistep process was followed, including (a) the translation and adaptation of the questionnaire, (b) a reliability analysis of the instrument’s items in combination with an exploratory factor analysis with 177 secondary school students, and (c) a confirmatory factor analysis for defining the underlying structure of the scale, using a sample of 532 secondary school students. The statistical analyses validated a 14-item version of the NfC-SF for measuring the cognitive motivation of secondary school, Greek-speaking students. The present study also extends previous research about the underlying structure of the NfC by suggesting that method effects should be considered in measurement models for improving scale validity.
Keywords: Cultural adaptation; Need for cognition; Scale validation; Wording effects